Pengaruh Ibnu Hazm dalam Pendidikan Islam di Andalus: Kontribusi Pemikiran dan Relevansi Kontemporer - Sindo, Pablo; Attoillah, Muhammad Farhan; Roza, Ellya (El-Idare, 2024)
This article discusses the influence of Ibn Hazm (384 H - 456 H) on Islamic education in Andalusia, one of the centers of Islamic civilization during the Middle Ages. Ibn Hazm is known as a great scholar who made significant contributions to the development of science, philosophy, and education. The focus of this research is to explore Ibn Hazm's ideas and thoughts related to education, particularly in aspects of teaching methodology, the integration of religious and general sciences, and character formation. This research uses a literature study method with a historical approach and descriptive analysis to identify Ibn Hazm's influence on Islamic education. The results show that Ibn Hazm emphasized the importance of rationality, freedom of thought, and the development of noble character in the educational process. Moreover, his ideas hold contemporary relevance in integrating ethical values with knowledge in modern education systems. The article concludes that Ibn Hazm's thoughts provide an important foundation for the renewal of Islamic education, both in the past and in the era of globalization.